'Grandpa Lives in Paradise Now': Biological Precarity and the Global Economy of Debility. Issue 1 (November 2015) - Kolářová, Kateřina
This paper examines the relations and the tensions between debility and disability in global contexts defined by complex forms of bio-social precarity. My focus is Baan Kamlangchay, in Thailand, a care home providing care for older people with dementia and Alzheimer's disease from the global North. I treat Baan Kamlangchay as one concrete example of emerging circuits of transnational care/reproductive labour in order to investigate the interrelations between disability and wider global bio-political inequalities. Using the concept of 'biolegitimacy', I discuss the power dynamics in the relationships between the racialised and gendered care workers in the centre and (white) disabled residents. I argue that debility, understood as the flexible gradation of dis/ability and in/capacity, allows us to better understand these novel forms of embodied precarity and their political implications in global contexts.